(untitled) (Clinics, 2014)
OBJECTIVE: The effects of acute continuous positive airway pressure therapy on left ventricular diastolic function and functional capacity in patients with compensated systolic heart failure remain unclear. METHODS: This randomized, double-blind, placebo-controlled clinical trial included 43 patients with heart failure and a left ventricular ejection fraction